High Entrepreneurship, Leadership, and Professionalism (HELP): Toward an Integrated, Empirically Based Perspective - Di Fabio, Annamaria; Bucci, Ornella; Gori, Alessio (Frontiers in Psychology, 2016)
This article evaluates the psychometric properties of a new measure for assessing the constructs of entrepreneurship, leadership, and professionalism, from an integrated point of view, the High Entrepreneurship, Leadership and Professionalism Questionnaire (HELP-Q). Exploratory factor analysis indicated a factor structure with three principal dimensions, and confirmatory factor analysis and goodness of fit indices indicated a good fit of the model to the data. All the dimensions showed good values of internal consistency. The results of the study thus indicate that the HELP-Q is a short and easily administered instrument with good psychometric properties that can promote entrepreneurship, leadership, and professionalism in workers as well as in those who are preparing to enter the turbulent 21st century labor market.